2020
DOI: 10.1186/s13039-020-0469-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 3387 umbilical cord blood in pregnant women at high risk for chromosomal abnormalities

Abstract: Background: Cordocentesis in our practice is most commonly indicated for rapid karyotyping in the second or third trimester and is regarded as the gold standard for foetal chromosomal aberration diagnosis in pregnancies at high risk for chromosomal abnormalities. In this study, we investigated 3387 umbilical cord blood samples for karyotyping from pregnant women who underwent cordocentesis and explored the pregnancy outcomes of foetal sex chromosome mosaicism and chromosomal polymorphism. Results: Out of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The number of patients who received invasive karyotyping and were diagnosed with chromosomal anomalies of the fetus after positive prenatal screening tests is 146 (20.6%). This rate was similar with the other publications in the literature [14,15].…”
Section: Discussionsupporting
confidence: 92%
“…The number of patients who received invasive karyotyping and were diagnosed with chromosomal anomalies of the fetus after positive prenatal screening tests is 146 (20.6%). This rate was similar with the other publications in the literature [14,15].…”
Section: Discussionsupporting
confidence: 92%
“…Others hold the opposite view that mosaicism in AF requires further cordocentesis for confirmation, and that the pregnancy is safe when a normal result is identified in CB. 29 There are a few drawbacks in our study. The first is our uncompleted long-term follow-up may lead to information loss for postnatal phenotypes.…”
Section: Discussionmentioning
confidence: 90%
“…Their results showed that CB and placentas were prone to a negative result when compared with AF, and array‐CGH on uncultured CB or FISH on cultured CB may be better to use for prenatal diagnosis. Others hold the opposite view that mosaicism in AF requires further cordocentesis for confirmation, and that the pregnancy is safe when a normal result is identified in CB 29 . These findings demonstrate that increased risk in genetic counselling is due to discordant CM from different specimens or testing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although not pathological per se, the incidence of ultrasound soft markers is higher in fetuses with chromosomal aberrations. (SUN et al, 2020;ALI et al, 2012;PARK et al, 2015) Major abnormalities are observed in 25% of fetuses with chromosomal abnormalities, whereas one or more soft markers may be observed in at least 50% of affected fetuses (RANIGA et al, 2006). The finding of one major structural malformation or two or more soft markers increases the risk for chromosomal aberrations in fetuses, and in these cases there is a necessity for genetic informing of patients, and invasive prenatal testing (BENN et al, 2015).…”
Section: Introductionmentioning
confidence: 99%